the properties of logs are the same as those of exponents.
√2 = 2^1/2
because
√2 * √2 = 2
and 2^a * 2^b = 2^(a+b)
2^1/2 * 2^1/2 = 2^1 = 2
And, 2^-n = 1/2^n
so,
1/√2 = 2^-1/2
I don't understand how log2 √(1/2) turned into log2 2^(-1/2).
Quote:
You will have to know the 3 prime properties of logs
1. logk (AB) = logk A + logk B
2. logk(A/B) = logk A - logk B
3. logk (A^n) = n logk A
where k is any positive number , k ≠ 1
so log2√36 - log2 log2</sub√72
= log2 (√36/√72)
= log2 √(36/72)
= log2 √(1/2)
= log2 2^(-1/2)
= (-1/2) log2 2
= (-1/2)(1)
= -1/2
1 answer